Sacrificial cathode material and lithium secondary battery including same

JP7607877B2Active Publication Date: 2025-01-06LG ENERGY SOLUTION LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2022558534
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-23
Filing Date
2022-02-10
Publication Date
2025-01-06
Estimated Expiration
2042-02-10

AI Technical Summary

Benefits of technology

【0028】 本発明による犠牲正極材は、特定金属がドープされ、密度汎関数理論(DFT)による前記金属の欠陥形成エネルギーが特定範囲内に制御されることによって、初期充放電時に高い初期充放電効率を具現し、以後、充放電時に追加的に発生するガス量を低減させることができるので、これを正極に含む電池の安定性と充放電性能を向上させる効果に優れているという利点がある。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007607877000005
    Figure 0007607877000005
  • Figure 0007607877000001
    Figure 0007607877000001
  • Figure 0007607877000002
    Figure 0007607877000002
Patent Text Reader

Abstract

The present invention relates to a sacrificial cathode material, a cathode including the same, and a lithium secondary battery including the same. The sacrificial cathode material is doped with a specific metal, and the defect formation energy of the metal is controlled within a specific range according to density functional theory (DFT). This allows the sacrificial cathode material to achieve high initial charge / discharge efficiency during initial charge / discharge and reduce the amount of additional gas generated during subsequent charge / discharge. This has the advantage of being excellent in improving the stability and charge / discharge performance of a battery including the same in its cathode.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sacrificial positive electrode material doped with a metal (M) such as Zn, Ge, Mg, or Si, and in which the metal (M) defect formation energy is controlled to a specific level, and a lithium secondary battery including the same.

[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0024259 filed on February 23, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference. [Background technology]

[0003] Recently, the demand for secondary batteries as an energy source has been increasing rapidly. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.

[0004] Graphite is mainly used as the negative electrode material for lithium secondary batteries, but since graphite has a small capacity per unit mass of 372 mAh / g, it is difficult to increase the capacity of lithium secondary batteries. For this reason, in order to increase the capacity of lithium secondary batteries, negative electrode materials that form intermetallic compounds with lithium, such as silicon, tin, and their oxides, have been developed and used as non-carbon-based negative electrode materials that have a higher energy density than graphite. However, such non-carbon-based negative electrode materials have a problem that, although they have a large capacity, their initial efficiency is low, resulting in a large amount of lithium consumption during initial charging and discharging, and a large irreversible capacity loss.

[0005] In this regard, a method has been proposed to overcome the irreversible capacity loss of the negative electrode by using a material that can provide a lithium ion source or reservoir for the positive electrode material and that is electrochemically active after the first cycle so as not to degrade the performance of the entire battery. Specifically, a method is known in which an oxide containing an excess amount of lithium, such as Li6CoO4, is applied to the positive electrode as a sacrificial positive electrode material or an irreversible additive (or over-discharge inhibitor).

[0006] However, such sacrificial cathode materials or irreversible additives have an unstable structure and may generate oxygen gas inside the battery due to oxidation during the battery activation stage as well as the subsequent charge and discharge process. The generated oxygen gas may induce volume expansion, which may be one of the main causes of deterioration of battery performance.

[0007] Therefore, there is a demand for the development of a sacrificial cathode material that exhibits high charge / discharge capacity. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Korean Patent Publication No. 10-2019-0059115 Summary of the Invention [Problem to be solved by the invention]

[0009] Accordingly, an object of the present invention is to provide a sacrificial cathode material that can improve irreversible capacity loss occurring in a negative electrode during initial charge / discharge, thereby realizing high initial charge / discharge efficiency, and reducing the amount of additional gas generated during subsequent charge / discharge, and a cathode and a lithium secondary battery including the same. [Means for solving the problem]

[0010] To solve the above problems, In one embodiment, the present invention comprises: The lithium cobalt oxide is represented by the following chemical formula 1: Provided is a sacrificial cathode material having a metal (M) defect formation energy of -4.0 to -8.5 eV according to density functional theory (DFT):

[0011] [Chemical formula 1] Li x Co (1-y) M y O4

[0012] In the above Chemical Formula 1, M is at least one selected from the group consisting of Al, Fe, Zn, Ti, W, Mg, Ge, Mn and Si; x and y are 5≦x≦7 and 0.05≦y≦0.6.

[0013] In this case, in the above Chemical Formula 1, M may be at least one selected from the group consisting of Mg, Ge, and Si, and y may be 0.2≦y≦0.4.

[0014] The sacrificial cathode material may have a defect formation energy of the metal (M) according to density functional theory (DFT) of -4.9 to -6.4 eV.

[0015] The sacrificial cathode material may also have a tetragonal structure with a space group of P42 / nmc.

[0016] The sacrificial cathode material is 5×10 -4 S / cm~1×10 -2 The powder may have a powder electrical conductivity of 0.1 S / cm.

[0017] In one embodiment, the present invention provides a method for producing a composition comprising: A positive electrode current collector; a positive electrode mixture layer on the positive electrode current collector, the positive electrode mixture layer including a positive electrode active material, a conductive material, an organic binder polymer, and a sacrificial positive electrode material; The sacrificial cathode material provides a cathode comprising a lithium cobalt oxide represented by the following chemical formula 1, in which the defect formation energy of the metal (M) according to density functional theory (DFT) is −4.0 to −8.5 eV:

[0018] [Chemical formula 1] Li x Co (1-y) M y O4

[0019] In the above Chemical Formula 1, M is at least one selected from the group consisting of Al, Fe, Zn, Ti, W, Mg, Ge, Mn and Si; x and y are 5≦x≦7 and 0.05≦y≦0.6.

[0020] Here, the content of the sacrificial positive electrode material may be 0.001 to 5.0 parts by weight with respect to 100 parts by weight of the positive electrode active material.

[0021] The content of the conductive material may be 0.5 to 10 parts by weight with respect to 100 parts by weight of the entire positive electrode mixture layer.

[0022] The conductive material may contain one or more carbonaceous materials selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fiber.

[0023] The positive electrode active material may contain two or more elements selected from the group consisting of nickel (Ni), cobalt (Co), manganese (Mn), aluminum (Al), zinc (Zn), titanium (Ti), magnesium (Mg), chromium (Cr), and zirconium (Zr).

[0024] In addition, the positive electrode mixture layer may have an average thickness of 100 μm to 200 μm.

[0025] In addition, the positive electrode may have a resistance change rate of 10% or less after 30 charge / discharge cycles compared to the resistance value at the initial charge / discharge cycle.

[0026] In one embodiment, the present invention provides an electrode assembly including the positive electrode described above.

[0027] In one embodiment, the present invention provides a lithium secondary battery including the electrode assembly. Effect of the Invention

[0028] The sacrificial cathode material according to the present invention is doped with a specific metal, and the defect formation energy of the metal according to density functional theory (DFT) is controlled within a specific range, thereby realizing high initial charge / discharge efficiency during initial charge / discharge and reducing the amount of additional gas generated during subsequent charge / discharge. Therefore, it has an advantage in that it is excellent in the effect of improving the stability and charge / discharge performance of a battery containing the same in the cathode. [Brief description of the drawings]

[0029] [Figure 1] 1 is a graph showing the initial charge capacity according to the type of metal doped in lithium cobalt oxide (LixCoO4, 5≦x≦7). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] Although the present invention can be modified in various ways and can have various embodiments, a specific embodiment will be described in detail in the detailed description. However, it should be understood that this is not intended to limit the invention to the particular embodiment, but rather to include all modifications, equivalents, or alternatives falling within the spirit and scope of the invention.

[0031] In the present invention, the terms "comprise" or "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and should be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0032] In addition, in the present invention, when a part such as a layer, film, region, or plate is described as being "on" another part, this includes not only the case where it is "directly on" the other part, but also the case where there is another part in between. Conversely, when a part such as a layer, film, region, or plate is described as being "under" the other part, this includes not only the case where it is "directly under" the other part, but also the case where there is another part in between. In addition, in the present application, being "located on" can include not only the case where it is located at the top, but also the case where it is located at the bottom.

[0033] The present invention will now be described in more detail.

[0034] Sacrificial cathode material In one embodiment, the present invention comprises: The lithium cobalt oxide is represented by the following chemical formula 1: Provided is a sacrificial cathode material having a metal (M) defect formation energy of -4.0 to -8.5 eV according to density functional theory (DFT):

[0035] [Chemical formula 1] Li x Co (1-y) M y O4

[0036] In the above Chemical Formula 1, M is at least one selected from the group consisting of Al, Fe, Zn, Ti, W, Mg, Ge, Mn and Si; x and y are 5≦x≦7 and 0.05≦y≦0.6.

[0037] The sacrificial cathode material according to the present invention contains, as a main component, lithium cobalt metal oxide represented by Chemical Formula 1. Here, the term "main component" means 80% by weight or more, 90% by weight or more, 95% by weight or more, or 97.5% by weight or more based on the total weight of the sacrificial cathode material, and in some cases, it can mean 100% by weight when the entire sacrificial cathode material is composed of lithium cobalt metal oxide represented by Chemical Formula 1.

[0038] The lithium cobalt metal oxide represented by the formula 1 is a lithium cobalt oxide (Li x CoO4, 5≦x≦7) may have a structure in which the cobalt sites are doped with one or more metals selected from the group consisting of Al, Fe, Zn, Ti, W, Mg, Ge, Mn, and Si, and specifically, may have a structure in which the cobalt sites are doped with one or more metals selected from the group consisting of Mg, Ge, and Si.

[0039] In this case, the amount of the metal doped may be 5 to 60 molar fraction (i.e., 0.05≦y≦0.6), specifically, 10 to 50 molar fraction (0.1≦y≦0.5); 15 to 50 molar fraction (0.15≦y≦0.5); 15 to 45 molar fraction (0.15≦y≦0.45); 20 to 40 molar fraction (0.2≦y≦0.4); or 25 to 35 molar fraction (0.25≦y≦0.35). By adjusting the amount of the metal doped to the above molar fraction range, the present invention can alleviate the structural twist of the lithium cobalt oxide, thereby further improving the structural stability.

[0040] In addition, the lithium cobalt metal oxide represented by the formula 1 may have a tetragonal crystal structure, and may have a space group of P42 / nmc. Generally, lithium metal oxides having a tetragonal crystal structure have a twisted rhombohedral structure formed by cobalt and oxygen elements, and have a structurally unstable structure. Due to this structural instability, gas containing oxygen gas is generated during charging after activation of the battery. However, the sacrificial cathode material of the present invention is a lithium cobalt oxide (Li x By having a structure in which one or more metals selected from the group consisting of Al, Fe, Zn, Ti, W, Mg, Ge and Si are doped at the cobalt sites of CoO4, 5≦x≦7), the effect of reducing the amount of gas generation can be exhibited even when the lithium cobalt metal oxide represented by Chemical Formula 1 having a tetragonal crystal structure is included.

[0041] The sacrificial positive electrode material may be one that is controlled so that the defect formation energy of the metal (M) according to density functional theory (DFT) satisfies a specific range. Specifically, the defect formation energy of the metal (M) according to density functional theory (DFT) of the sacrificial positive electrode material may be -4.0 to -8.5 eV, more specifically, -4.0 to -7.0 eV; -4.0 to -6.5 eV; -4.5 to -7.0 eV; -4.9 to -6.4 eV; -5.0 to -6.0 eV; -4.5 to -5.6 eV; -5.0 to -5.5 eV; -5.5 to -5.9 eV; or -6.0 to -6.5 eV. The defect formation energy of the metal (M) may be controlled so that the defect formation energy of the metal (M) according to density functional theory (DFT) of the sacrificial positive electrode material satisfies a specific range. x By controlling the defect formation energy of the metal (M) within the above range, the present invention can improve the structural stability of the sacrificial cathode material and reduce the amount of gas generated during initial charge and discharge and the cumulative amount of gas generated thereafter.

[0042] The sacrificial positive electrode material is a lithium cobalt metal oxide represented by the chemical formula 1, which is 5×10 -4 S / cm~1×10 -2 The powder may have a powder electrical conductivity of 5×10 S / cm. -4 S / cm~1×10 -3 S / cm; 5×10 -4 S / cm~1×10 -2 S / cm; 5×10 -4 S / cm~5×10 -3 S / cm; 8×10 -4 S / cm~9×10 -3 S / cm; 1×10 -3 S / cm~8×10 -3 S / cm; 6.0×10 -3 S / cm~7.5×10 -3 S / cm; or 3.5×10 -3 S / cm~6.5×10 -3 The powder electrical conductivity of the sacrificial positive electrode material may be 10 -7Lithium cobalt oxide (Li) has a remarkably low powder electrical conductivity of less than 1.5 S / cm. x The doping amount of the metal (M) doped at the cobalt site of CoO4, 5≦x≦7) and the manufacturing conditions of the sacrificial cathode material can be adjusted. By adjusting the powder electrical conductivity within the above range, the amount of gas generated during charging of the battery can be reduced and the charge / discharge capacity can be further improved.

[0043] As described above, the sacrificial cathode material according to the present invention includes a lithium-cobalt metal oxide represented by Chemical Formula 1 doped with a specific metal, and the defect formation energy of the metal is controlled within a specific range according to density functional theory (DFT), thereby realizing high initial charge / discharge efficiency during initial charge / discharge and reducing the amount of additional gas generated during subsequent charge / discharge. Therefore, it has an advantage in that it is excellent in the effect of improving the stability and charge / discharge performance of a battery including the same in the cathode.

[0044] positive electrode In one embodiment, the present invention provides a method for producing a composition comprising: A positive electrode current collector; a positive electrode mixture layer on the positive electrode current collector, the positive electrode mixture layer including a positive electrode active material, a conductive material, an organic binder polymer, and a sacrificial positive electrode material; The sacrificial cathode material provides a cathode comprising a lithium cobalt oxide represented by the following chemical formula 1, in which the defect formation energy of the metal (M) according to density functional theory (DFT) is −4.0 to −8.5 eV:

[0045] [Chemical formula 1] Li x Co (1-y) M y O4

[0046] In the above Chemical Formula 1, M is at least one selected from the group consisting of Al, Fe, Zn, Ti, W, Mg, Ge, Mn and Si; x and y are 5≦x≦7 and 0.05≦y≦0.6.

[0047] The positive electrode according to the present invention has a structure in which a positive electrode composite layer is formed on a positive electrode current collector, and the positive electrode composite layer contains the above-mentioned sacrificial positive electrode material of the present invention in addition to a positive electrode active material; a conductive material; and an organic binder polymer, and has a high charge / discharge capacity and is excellent in reducing gas, particularly oxygen (O2) gas, generated during charging and discharging of a battery.

[0048] Here, the positive electrode active material may be a lithium composite transition metal oxide containing two or more elements selected from the group consisting of nickel (Ni), cobalt (Co), manganese (Mn), aluminum (Al), zinc (Zn), titanium (Ti), magnesium (Mg), chromium (Cr) and zirconium (Zr). For example, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) or a layered compound substituted with one or more transition metals; 1+x Mn 2-x Lithium manganese oxides such as LiMnO3, LiMn2O3, and LiMnO2; lithium copper oxides such as Li2CuO2; vanadium oxides such as LiV3O8, LiFe3O4, V2O5, and Cu2V2O7; and the chemical formula LiNi 1-x M x Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (where M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x=0.01 to 0.3); 2-x M x Lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M=Co, Ni, Fe, Cr, Zn or Ta, and x=0.01 to 0.1) or Li2Mn3MO8 (wherein M=Fe, Co, Ni, Cu or Zn); LiNi x Mn 2-x Examples include lithium manganese oxides with a spinel structure represented by O4; LiMn2O4, in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion; disulfide compounds; and Fe2(MoO4)3.

[0049] The sacrificial positive electrode material may be included in an amount of 0.001 to 5.0 parts by weight relative to 100 parts by weight of the positive electrode active material. More specifically, the sacrificial positive electrode material may be included in an amount of 0.001 to 4.0 parts by weight, 0.001 to 3.0 parts by weight, 0.001 to 2.0 parts by weight, 0.001 to 1.0 parts by weight, 0.01 to 2.0 parts by weight, 0.05 to 2.0 parts by weight, 0.1 to 2.0 parts by weight, or 0.1 to 1.5 parts by weight relative to 100 parts by weight of the positive electrode active material.

[0050] The conductive material may be added in an amount of 1 to 20 parts by weight relative to 100 parts by weight of the positive electrode active material, and specifically, the conductive material may be added in an amount of 1 to 10 parts by weight, 1 to 5 parts by weight, 3 to 8 parts by weight, or 2 to 5 parts by weight relative to 100 parts by weight of the positive electrode active material.

[0051] Furthermore, such a conductive material is not particularly limited as long as it is conductive without inducing a chemical change in the battery, and examples of such conductive materials that can be used include graphite such as natural graphite and artificial graphite; carbon black such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fiber and metal fiber; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0052] The organic binder polymer is a component that assists in binding between the active material and the conductive material and between the active material and the current collector, and may be added in an amount of 1 to 20% by weight relative to 100 parts by weight of the positive electrode active material. Specifically, the organic binder polymer may be added in an amount of 1 to 10 parts by weight, 1 to 5 parts by weight, 3 to 8 parts by weight, or 2 to 5 parts by weight relative to 100 parts by weight of the positive electrode active material.

[0053] Examples of such organic binder polymers include polyvinylidene fluoride (PVdF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diether polymer (EPDM), sulfonated EPDM, styrene-butylene rubber, fluororubber, and various copolymers.

[0054] In addition, the positive electrode may further include a filler for suppressing the expansion of the positive electrode in the positive electrode mixture layer in addition to the positive electrode active material, the conductive material, and the organic binder polymer, and such a filler is not particularly limited as long as it is a fibrous material that does not induce chemical changes in the battery. Specifically, the filler may be an olefin polymer such as polyethylene or polypropylene; or a fibrous material such as glass fiber or carbon fiber.

[0055] As an example, the positive electrode mixture layer is made of lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2) 100 parts by weight of sacrificial cathode material (Li6Co 0.7 Zinc 0.3 O4) 1 part by weight; acetylene black, which is a conductive material, 5 parts by weight; and binder (PVdF) 10 parts by weight.

[0056] The positive electrode mixture layer may have an average thickness of 100 μm to 200 μm, specifically, 120 μm to 180 μm; 140 μm to 170 μm; or 150 μm to 200 μm.

[0057] In addition, the positive electrode mixture layer may be a single layer or may have a multi-layer structure of two or more layers. When the positive electrode mixture layer has a multi-layer structure of two or more layers, the sacrificial positive electrode material contained in the positive electrode mixture layer may have different contents; the positive electrode active material, conductive material, and binder may be the same or different in type and / or content.

[0058] For example, the positive electrode mixture layer may have a two-layer structure in which a first mixture layer and a second mixture layer are sequentially laminated on a positive electrode current collector, and the first mixture layer may be made of lithium nickel cobalt manganese oxide (LiNi 0.8 Co 0.1 Mn 0.1 O2) 100 parts by weight of sacrificial cathode material (Li6Co 0.7 Zinc 0.3 O4) 1 part by weight; acetylene black as a conductive material 5 parts by weight; and binder (PVdF) 10 parts by weight. The second composite layer is made of lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2) 100 parts by weight of sacrificial cathode material (Li6Co 0.7 Zinc 0.3 O4) 2 parts by weight; acetylene black, which is a conductive material, 5 parts by weight; and binder (PVdF) 9 parts by weight.

[0059] In addition, when the positive electrode mixture layer has a two-layer structure in which a first mixture layer and a second mixture layer are sequentially laminated on a positive electrode current collector, each layer can satisfy the following formula 1:

[0060] [Formula 1] 0.05≦SCM 1st / SCM 2nd ≦0.9

[0061] In the above formula 1, SCM 1st indicates the content of the positive electrode additive contained in the first positive electrode mixture layer, SCM 2nd indicates the content of the positive electrode additive contained in the second positive electrode mixture layer.

[0062] The formula 1 indicates the ratio of the positive electrode additive contained in each of the first and second positive electrode mixture layers, and means that the content of the positive electrode additive contained in the second positive electrode mixture layer, i.e., the content of the lithium cobalt oxide represented by formula 1, is greater than the content of the positive electrode additive contained in the first positive electrode mixture layer. The positive electrode mixture layer according to the present invention satisfies the above formula 1 in the range of 0.05 to 0.9 (for example, 0.05≦SCM 1st / SCM 2nd ≦0.9), specifically, 0.1 to 0.9 (for example, 0.1≦SCM 1st / SCM 2nd ≦0.9), 0.2~0.8 (for example, 0.2≦SCM 1st / SCM 2nd ≦0.8), 0.3~0.7 (for example, 0.3≦SCM 1st / SCM 2nd ≦0.7) or 0.4~0.8 (e.g., 0.4≦SCM 1st / SCM 2nd The positive electrode mixture layer according to the present invention satisfies the condition of Formula 1, thereby further improving the irreversible reaction efficiency of the positive electrode additive during initial charging, and thus reducing gas generation during charging and discharging after the initial charging and discharging.

[0063] In addition, the positive electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and for example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. can be used, and in the case of aluminum or stainless steel, it may be surface-treated with carbon, nickel, titanium, silver, etc. In addition, the positive electrode current collector can be formed with fine irregularities on the surface to increase the adhesive force of the positive electrode active material, and can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc. In addition, the average thickness of the positive electrode current collector can be appropriately applied to 3 to 500 μm in consideration of the conductivity and total thickness of the positive electrode to be manufactured.

[0064] In addition, the positive electrode according to the present invention has excellent electrical performance due to the above-mentioned composition. Specifically, the positive electrode has low electrode resistance at room temperature (23±2° C.), and even after repeated charging and discharging of the battery, the amount of change in electrode resistance is small, thereby improving the battery life.

[0065] For example, the positive electrode may have a low resistance change rate of 10% or less after 30 charge / discharge cycles compared to the electrode resistance value during initial charge / discharge (e.g., activation stage). For example, the positive electrode may have an electrode resistance change rate of 8% or less, 6% or less, 4% or less, or 3% or less after initial charge / discharge and 30 charge / discharge cycles.

[0066] electrode assembly In one embodiment, the present invention provides an electrode assembly including the positive electrode described above.

[0067] The electrode assembly according to the present invention may have a structure including the above-mentioned positive electrode, negative electrode, and a separator interposed between the positive electrode and the negative electrode, and in some cases, the separator may be omitted.

[0068] Here, the negative electrode is prepared by applying a negative electrode active material onto a negative electrode current collector, drying and pressing the same, and may further selectively include the same conductive material, organic binder polymer, filler, etc. as described above, as necessary.

[0069] In addition, examples of the negative electrode active material include graphite having a perfect layered crystal structure such as natural graphite, soft carbon having a low-crystalline layered crystal structure (graphene structure; a structure in which hexagonal honeycomb-shaped planes of carbon are arranged in layers), and hard carbon in which such a structure is mixed with an amorphous portion, artificial graphite, expanded graphite, carbon fiber, carbon that is difficult to graphitize, carbon black, carbon nanotubes, fullerenes, activated carbon, and other carbon and graphite materials; metal composite oxides such as LixFe2O3 (0 ≦ x ≦ 1), LixWO2 (0 ≦ x ≦ 1), SnxMe1-xMe′yOz (Me: Mn, Fe, Pb, Ge; Me′: Al, B, P, Si, Group 1, Group 2, Group 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8); lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; metal oxides such as SnO, SnO2, PbO, PbO2, Pb2O3, Pb3O4, Sb2O3, Sb2O4, Sb2O5, GeO, GeO2, Bi2O3, Bi2O4, and Bi2O5; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides, etc. can be used.

[0070] In addition, the negative electrode current collector is not particularly limited as long as it has high conductivity without inducing a chemical change in the battery. For example, copper, stainless steel, nickel, titanium, fired carbon, etc. can be used. In the case of copper or stainless steel, those surface-treated with carbon, nickel, titanium, silver, etc. may be used. Further, similar to the positive electrode current collector, the negative electrode current collector can also form fine irregularities on the surface to strengthen the bonding force with the negative electrode active material, and various forms such as films, sheets, foils, nets, porous bodies, foams, non-woven bodies, etc. are possible. Further, the average thickness of the negative electrode current collector can be appropriately applied in the range of 3 to 500 μm in consideration of the conductivity and total thickness of the manufactured negative electrode.

[0071] The separator is a thin insulating membrane interposed between the positive and negative electrodes and having high ion permeability and mechanical strength. The separator is not particularly limited as long as it is one commonly used in the industry, and specifically, a sheet or nonwoven fabric made of chemically resistant and hydrophobic polypropylene, glass fiber, or polyethylene may be used. In some cases, a composite separator may be used in which inorganic particles / organic particles are coated with an organic binder polymer on a porous polymer substrate such as the sheet or nonwoven fabric. When a solid electrolyte such as a polymer is used as the electrolyte, the solid electrolyte may also serve as the separator. The pore diameter of the separator may be an average of 0.01 to 10 μm, and the thickness may be an average of 5 to 300 μm.

[0072] Meanwhile, the electrode assembly may be wound in a jelly roll form and housed in a cylindrical battery, a prismatic battery, or a pouch-type battery, or may be housed in a pouch-type battery in a folded or stack-and-folded form, but is not limited thereto.

[0073] Lithium secondary battery In one embodiment, the present invention provides a lithium secondary battery including the above-mentioned electrode assembly.

[0074] The lithium secondary battery according to the present invention may have a structure in which the electrode assembly is impregnated with an electrolyte solution containing a lithium salt.

[0075] In this case, the lithium salt-containing electrolyte may be composed of an electrolyte and a lithium salt, and the electrolyte may be a non-aqueous organic solvent, an organic solid electrolyte, an inorganic solid electrolyte, or the like.

[0076] Examples of non-aqueous organic solvents that can be used include aprotic organic solvents such as N-methyl-2-pyrrolidinone, ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydroxyfuran (franc), 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0077] Examples of the organic solid electrolyte that can be used include polyethylene derivatives, polyethylene oxide derivatives, polypropylene oxide derivatives, phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymeric materials containing ionic dissociation groups.

[0078] Examples of inorganic solid electrolytes that can be used include nitrides, halides, and sulfates of Li, such as Li3N, LiI, Li5Ni2, Li3N-LiI-LiOH, LiSiO4, LiSiO4-LiI-LiOH, Li2SiS3, Li4SiO4, Li4SiO4-LiI-LiOH, and Li3PO4-Li2S-SiS2.

[0079] Lithium salts are substances that are easily dissolved in non-aqueous electrolytes, such as LiCl, LiBr, LiI, LiClO4, LiBF4, and LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi, lithium chloroborane, lithium lower aliphatic carboxylates, lithium tetraphenylboronate, imides, etc. can be used.

[0080] In addition, for the purpose of improving charge / discharge characteristics, flame retardancy, etc., the electrolyte may contain, for example, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. In some cases, in order to impart non-flammability, a halogen-containing solvent such as carbon tetrachloride or trifluoroethylene may be further contained, and in order to improve high-temperature storage characteristics, carbon dioxide gas may be further contained, and fluoroethylene carbonate (FEC), propene sultone (PRS), etc. may be further contained.

[0081] Meanwhile, in one embodiment, the present invention provides a battery module including the above-mentioned secondary battery as a unit cell, and provides a battery pack including the battery module.

[0082] The battery pack can be used as a power source for medium- to large-sized devices that require high temperature stability, long cycle characteristics, and high rate characteristics. Specific examples of such medium- to large-sized devices include power tools that are driven by electric motors; electric vehicles, including electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems, and more specifically, examples thereof include, but are not limited to, hybrid electric vehicles (HEVs).

[0083] The present invention will now be described in more detail with reference to examples and experimental examples.

[0084] However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.

[0085] Examples 1 to 11. Preparation of sacrificial cathode materials Lithium oxide (Li2O), cobalt oxide (CoO), and metal oxides (MO) shown in Table 1 below were put into a reactor and uniformly dry-mixed for about 30 minutes using a mixer. The raw material mixture was then placed in an electric furnace and fired at about 700±10°C for 10 hours under argon gas (Ar) conditions to produce lithium cobalt oxide (Li6Co 1-y M y O4).

[0086] At this time, the molar ratio of lithium oxide and cobalt oxide fed into the reactor was 1:3.0~3.03, and i) the type of metal oxide (MO) and ii) the molar ratio of cobalt oxide and metal oxide (MO) were as shown in Table 1 below. Each of the produced sacrificial materials was analyzed for (1) the defect formation energy of the doped metal (M) and (2) the powder electrical conductivity.

[0087] Specifically, in the case of (1) metal (M) defect formation energy, calculations were performed using density functional theory (DFT). The density functional theory (DFT) calculations were performed using the Vienna ab initio simulation package (VASP) to calculate the atomic and electronic structures and energies using the projector-augmented wave (PAW) method; the electronic exchange-correlation functional was calculated using the Perdew, Burke, Ernzerhof (PBE) model method based on generalized gradient approximation (GGA); the kinetic energy cutoff was set to 500 eV; and the 2X2X3 Monkhorst-Pack method was used for the surface of each metal (M).

[0088] In addition, (2) to measure the powder electrical conductivity of the sacrificial cathode material, each manufactured sacrificial cathode material was compressed to produce a powder. Then, the volume of each sacrificial cathode material and the surface resistance due to pressure change were measured using a powder resistance characteristic measuring device using a 4-point probe method for the manufactured powder, and the powder electrical conductivity of the sacrificial cathode material was calculated using the measured volume and input mass. The measurement results are shown in Table 1 below.

[0089] [Table 1]

[0090] Comparative Examples 1 to 3. Production of sacrificial cathode materials The same method as in Example 1 was used, but the type of i) metal oxide (MO) mixed with lithium oxide (Li2O) and cobalt oxide (CoO) and the molar ratio of ii) cobalt oxide to metal oxide were adjusted as shown in Table 2 below, and lithium cobalt oxide (Li6Co 1-y M y O4).

[0091] In this case, (1) the defect formation energy of the doped metal (M) and (2) the powder electrical conductivity of the prepared sacrificial cathode material were analyzed in the same manner as in the Examples, and the results are shown in Table 2 below.

[0092] [Table 2]

[0093] Experimental example. In order to evaluate the performance of the sacrificial cathode material prepared according to the present invention, the following experiment was carried out.

[0094] B) Initial charge / discharge capacity and efficiency evaluation N-methylpyrrolidone solvent was poured into a homomixer, and the sacrificial cathode materials prepared in Examples 1 to 10 and Comparative Examples 1 to 3, acetylene black conductive material, modified silanol binder, and dispersant were added in a weight ratio of 95:3:1.7:0.3, and mixed at 3,000 rpm for 60 minutes to prepare a pre-dispersion solution.

[0095] The content of the sacrificial cathode material is the cathode active material (LiNi 0.6 Co 0.2 Mn 0.2 O2) A pre-dispersion liquid prepared to be 2 parts by weight per 100 parts by weight of the positive electrode active material was mixed, and the positive electrode active material mixed in N-methylpyrrolidone solvent, PVdF as a binder, and carbon black as a conductive material were added to a homo mixer to a weight ratio of 96:1:3, and dispersed at 3,000 rpm for 80 minutes to prepare a positive electrode slurry. The prepared positive electrode slurry was applied to one side of an aluminum current collector, dried at 100°C, and rolled to prepare a positive electrode.

[0096] A 2032-type coin cell was manufactured using the positive electrode and lithium metal counter electrode. A separator (thickness: about 16 μm) made of a porous polyethylene (PE) film was placed between the positive electrode and the lithium metal counter electrode, and an electrolyte was injected to manufacture a coin cell in the form of a half cell.

[0097] In this case, E2DVC was used as the electrolyte. Here, "E2DVC" refers to a carbonate-based electrolyte, which is a solution obtained by mixing lithium hexafluorophosphate (LiPF6, 1.0M) and vinyl carbonate (VC, 2% by weight) in a mixture of ethylene carbonate (EC): dimethyl carbonate (DMC): diethyl carbonate (DEC) = 1:1:1 (volume ratio).

[0098] The fabricated coin cell was subjected to initial charge / discharge formation under a reference capacity condition of 200mAh / 200mAh at 25°C, and the initial charge capacity and initial discharge capacity were measured. The efficiency was calculated from the measured initial charge / discharge capacity, and the results are shown in Table 3 below.

[0099] [Table 3]

[0100] As shown in Table 3, the sacrificial cathode material according to the present invention has a high initial charge capacity during the initial charge / discharge and exhibits high initial charge / discharge efficiency.

[0101] B) Evaluation of the amount of gas generated after the initial charge and discharge The coin cell used above was charged and discharged 50 times at 45℃ and 0.3C / 0.3C, and the amount of gas generated during each charge and discharge was measured, and the cumulative amount of gas generated after the initial charge and discharge was calculated. The results are shown in Table 4 below.

[0102] [Table 4]

[0103] It can be seen that the sacrificial cathode material according to the present invention reduces the amount of gas generated by charging and discharging after the initial charging and discharging.

[0104] Specifically, the sacrificial cathode material of the embodiment had a low cumulative gas generation amount of 7.5 mL / g or less due to charging and discharging after the initial charging and discharging, while the sacrificial cathode material of the comparative example had a high cumulative gas generation amount of 7.5 mL / g or more.

[0105] From these results, the sacrificial cathode material according to the present invention is doped with a specific metal, and the defect formation energy of the metal according to density functional theory (DFT) is controlled within a specific range, thereby realizing high initial charge / discharge efficiency during initial charge / discharge and reducing the amount of additional gas generated during subsequent charge / discharge. Therefore, it can be seen that the sacrificial cathode material according to the present invention has an excellent effect of improving the stability and charge / discharge performance of a battery including the same in the cathode.

[0106] Although the present invention has been described above with reference to preferred embodiments, it will be understood that a person skilled in the art or having ordinary knowledge in the art can make various modifications and variations to the present invention without departing from the spirit and technical scope of the present invention as described in the claims below.

[0107] Therefore, the technical scope of the present invention should not be limited to the contents described in the detailed description of the specification, but should be defined by the claims.

Claims

1. The lithium cobalt oxide is represented by the following formula 1: A sacrificial cathode material having a metal (M) defect formation energy of −4.0 to −8.5 eV according to density functional theory (DFT): [Chemical formula 1] Li x Co (1-y) M y O 4 In the above Chemical Formula 1, M is at least one selected from the group consisting of Fe, Ti, W, Mg, Ge and Si; x and y are within the range of 5≦x≦7 and 0.05≦y≦0.

6.

2. 2. The sacrificial cathode material of claim 1, wherein M is at least one selected from the group consisting of Mg, Ge, and Si.

3. The sacrificial cathode material of claim 1 or 2, wherein y in the formula 1 satisfies 0.2≦y≦0.

4.

4. The lithium cobalt oxide is represented by the following formula 1: The defect formation energy of the metal (M) according to density functional theory (DFT) is −4.0 to −8.5 eV; The powder electrical conductivity is 3.5×10 -3 S / cm~6.5×10 -3 S / cm, a sacrificial cathode material: [Chemical formula 1] Li x Co (1-y) M y O 4 In the above Chemical Formula 1, M is at least one selected from the group consisting of Al and Zn; x and y are within the range of 5≦x≦7 and 0.05≦y≦0.

6.

5. A lithium cobalt oxide having the following chemical formula 1: A sacrificial cathode material having a metal (M) defect formation energy of −4.0 to −8.5 eV according to density functional theory (DFT): [Chemical formula 1] Li x Co (1-y) M y O 4 In the above Chemical Formula 1, M is Mn; x and y are within the range of 5≦x≦7 and 0.1≦y≦0.

6.

6. The sacrificial cathode material according to any one of claims 1 to 5, wherein the defect formation energy of the metal (M) by density functional theory (DFT) of the sacrificial cathode material is -4.9 to -6.4 eV.

7. 7. The sacrificial cathode material of claim 1, wherein the sacrificial cathode material has a tetragonal structure with a space group of P42 / nmc.

8. The sacrificial cathode material is 5×10 -4 S / cm to 1×10 -2 8. The sacrificial cathode material of any one of claims 1 to 3 and 5 to 7 having a powder electrical conductivity of 0.1 S / cm.

9. A positive electrode current collector; A positive electrode comprising: a positive electrode mixture layer on the positive electrode current collector, the positive electrode mixture layer comprising a positive electrode active material, a conductive material, an organic binder polymer, and the sacrificial positive electrode material according to any one of claims 1 to 8.

10. The positive electrode according to claim 9, wherein the content of the sacrificial positive electrode material is 0.001 to 5.0 parts by weight per 100 parts by weight of the positive electrode active material.

11. The positive electrode according to claim 9 or 10, wherein the content of the conductive material is 0.5 to 10 parts by weight per 100 parts by weight of the total positive electrode mixture layer.

12. The positive electrode according to any one of claims 9 to 11, wherein the conductive material comprises one or more carbon-based materials selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fiber.

13. The positive electrode according to any one of claims 9 to 12, wherein the positive electrode active material is a lithium composite transition metal oxide containing two or more elements selected from the group consisting of nickel (Ni), cobalt (Co), manganese (Mn), aluminum (Al), zinc (Zn), titanium (Ti), magnesium (Mg), chromium (Cr), and zirconium (Zr).

14. The positive electrode according to any one of claims 9 to 13, wherein the positive electrode mixture layer has an average thickness of 100 µm to 200 µm.

15. An electrode assembly comprising the positive electrode according to any one of claims 9 to 14.

16. A lithium secondary battery comprising the electrode assembly according to claim 15.

Citation Information

Patent Citations

  • Positive plate, preparation method and lithium-ion battery comprising positive plate

    CN107706351A

  • Positive electrode additive, method for producing the same, positive electrode and lithium secondary battery containing the same

    JP2020521285A

  • Irreversible Additive Comprised in Cathode Material for Lithium Secondary Battery, Preparing Method thereof, and Cathode Material Comprising the Same

    KR1020190059115A

  • Positive electrode additive material for rechargeable lithium battery, method of preparing the same, positive electrode including the same and rechargeable lithium battery including the same

    KR1020200066048A

  • Anode for lithium secondary battery and lithium secondary battery comprising the same

    KR1020210015141A